Memory-like CD8+ T cells lacking PD-1 adapt to persistent stimulation by reducing TCR signal transduction rather than increasing exhaustion - Charmoy, Mélanie; Maier, Julia M.; Wyss, Tania; Chennupati, Vijaykumar; Sabatel, Catherine; Bonneaux, Laurie; Dumez, Alexandre; Veber, Romain; Guarda, Greta; Held, Werner (Frontiers in Immunology, 2026)
CD8+ T cells respond to persistent stimulation during chronic viral infection by stably expressing co-inhibitory receptors and other exhaustion-related molecules. Here we addressed how memory-like CD8+ T (TML) cells, which sustain the immune response to chronic infection thanks to their stem-like properties, adapt to chronic stimulation when they cannot express the co-inhibitory receptor PD-1. We found an increased initial generation and stable long-term persistence of TML cells lacking PD-1 during chronic viral infection. However, these cells had a reduced ability regenerate upon acute restimulation in the context of a recall response. Mechanistically, the lack of PD-1-mediated inhibition was not compensated by an increased expression of other co-inhibitory receptors or exhaustion related molecules. Rather, the absence of PD-1 resulted in a reduced capacity of the TCR to activate TML cells and to express stemness genes including Myb and Klf4. Similar albeit weaker effects on TML cells were noted when PD-1 engagement was transiently interrupted due to anti-PD-L1 treatment. Thus, stem-like CD8+ T cells responding to chronic viral infection adapt to the absence of PD-1-dependent co-inhibitory signals by further reducing TCR-mediated activation signaling, likely to prevent excessive or prolonged stimulation of these cells.